Investigating relationship between traffic density and particulate matter concentrations - Mohd Aminuddin, Muhammad Farhan Afiq (2023)
Air pollution have been shown in many studies to cause many health adverse effects. The researcher aims to investigate the relationship between traffic density and particulate matter concentrations which is conducted by the roadside in Gong Badak, Terengganu. The road is situated near public amenities such as food stalls, kindergarten and homestay. The sampling is conducted for 4 hours from 8.00 a.m. to 12.00 p.m. using Dust Trax TM DRX Aerosol Monitor 8534. The study aims to determine the trend of particulate matter concentrations at study areas and to establish relationship between number of motor vehicles and concentrations of particulate matter. The distribution trend across all PM10 , PM2.5 , PM1 is almost the same which is low at 8 a.m. and slowly increasing and peak at 10 a.m. and start to decrease at 11a.m. During the study period, the overall average (mean of 4 hours of data) concentrations of PM1 (ultra-fine), PM2.5 (fine) and PM10 (coarse) were 0.054 mgm⁻³ , 0.055 mgm⁻³ and 0.064 mgm⁻³ , respectively. The mean of PM2.5 concentrations (55 μgm⁻³ ) were higher than the daily National Ambient Air Quality Standards, while the PM10 concentrations (64 μgm ) are lower than the NAAQS (NAAQS: PM2.5 = 35 μgm⁻³ & PM10 =150 μgm⁻³ ). However, results show a weak correlation between concentration of particulate matter and number of motor vehicles with R values 0.154, 0.157 and 0.152 for PM10 , PM2.5 and PM1 , respectively. In conclusion, the distribution trend across all PM10 , PM2.5 , PM1 is almost the same which is low at 8 a.m. and slowly increasing and peak at 10 a.m. and start to decrease at 11a.m. Meanwhile the relationship between traffic density and concentration of particulate matter results show that the concentration of particulate matter has a positive but weak relation with the number of motor vehicles. Future studies can do on relationship of traffic density and concentration of particulate matter in other part of Malaysia to give a better understanding about traffic related pollution in Malaysia.